FSQM 2020
DOI: 10.7176/fsqm/93-03
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Some Biochemical Contents of Coffee Arabica (Coffea arabica L.) Varieties and Correlation with Organoleptic Cup Quality in Contrasting Altitudes in Southwest Ethiopia

Abstract: Coffee is one of the most important agricultural commodities. The objective of this study was to simultaneously determination the biochemical constituents (caffeine, chlorogenic and nicotinic acids) and correlation with organoleptic cup quality of commonly grown coffee Arabica varieties in contrasting altitude of Southwest Ethiopia. A rapid and validated HPLC Diode Array Detector method was used for the simultaneous determination of targeted analytse in green and roasted coffee beans. The moisture content and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
0
0
2
Order By: Relevance
“…The higher concentrations of NA in traditional coffees, before roasting, may result from the way of cultivation and processing, as nutritional deficiency, diseases, poor handling during harvest, and different types of processing tend to produce lower quality coffees with varying characteristics of flavor (Feria‐Morales, 2002; Kleinwächter et al., 2015; Macrae, 1985). The literature itself reports that the NA content can vary from 0.002 to 1016 mg 100 g −1 of green coffee (Bressani & Navarrete, 1959; Casal et al., 1998, 2000; Chirfa et al., 2020; Girma, 2020; Girma et al., 2020; Mazzafera, 1991), which is consistent with the levels found.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The higher concentrations of NA in traditional coffees, before roasting, may result from the way of cultivation and processing, as nutritional deficiency, diseases, poor handling during harvest, and different types of processing tend to produce lower quality coffees with varying characteristics of flavor (Feria‐Morales, 2002; Kleinwächter et al., 2015; Macrae, 1985). The literature itself reports that the NA content can vary from 0.002 to 1016 mg 100 g −1 of green coffee (Bressani & Navarrete, 1959; Casal et al., 1998, 2000; Chirfa et al., 2020; Girma, 2020; Girma et al., 2020; Mazzafera, 1991), which is consistent with the levels found.…”
Section: Resultssupporting
confidence: 81%
“…flavor (Feria-Morales, 2002;Kleinwächter et al, 2015;Macrae, 1985). The literature itself reports that the NA content can vary from 0.002 to 1016 mg 100 g −1 of green coffee (Bressani & Navarrete, 1959;Casal et al, 1998Casal et al, , 2000Chirfa et al, 2020;Girma, 2020;Girma et al, 2020;Mazzafera, 1991), which is consistent with the levels found. 5-HMF (has a sensory threshold of 100 ppm, herbaceous aroma, similar to hay, and close to tobacco, in addition to a bitter and musty taste depending on concentration) is a marker of heat treatment in foods, but presence in green coffee beans still is conflicting in the literature (Alcantara et al, 2021;Fowble et al, 2019).…”
Section: Samplessupporting
confidence: 82%
“…Напитки, приготовленные из обжаренных семян кофе (Coffea L.), относятся к наиболее популярным во всем мире, причем реально употребляются семена двух видов кофе -арабика (C. arabica L.) и робуста (С. canefora P.). Ежегодный рынок производимого более чем в 18 странах кофе оценивается в 14 миллиардов долларов [1]. Качество напитка, приготавливаемого из обжаренных семян, имеет важнейшее значение при оценке стоимости сырья.…”
unclassified
“…Но наиболее важными прекурсорами запаха являются сахара -особенно сахароза. В работе [1] было установлено, что при изменении содержания кофеина от 14 мг на (здесь и далее на 1 г обжаренного кофе) до почти 21 мг качество падает от высокого до низкого. Аналогично качество снижалось при росте содержания хлорогеновых кислот от 8,56 мг до 16,21 мг, и повышалось только при росте содержания никотиновой кислоты с 7,13 мг до 10,16 мг.…”
unclassified